2019
DOI: 10.4314/sajas.v49i5.16
|View full text |Cite
|
Sign up to set email alerts
|

Safflower seeds in the diet of feedlot lambs improved fat carcass, colour, and fatty acid profile of the meat

Abstract: The aim of this study was to evaluate intake, performance, carcass characteristics and meat quality of lambs fed finishing diets containing 0%, 7.5% and 15% safflower seeds (Carthamus tinctorius) as a replacement for corn and soybean meal. Thirty-six male lambs with mean bodyweight of 17.9 ± 1.8 kg were randomly assigned to one of three treatments: C0: no safflower seeds, C7.5: 7.5%safflower seeds in diet (DM basis), and C15: 15% safflower seeds in diet (DM basis). The lambs were fed in pens of two and thus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The inclusion of ALA-rich sources (linseed, chia seed and camelina oil) did not affect growth and carcass parameters, either in light [ 1 , 2 , 13 , 14 ] or heavy lambs [ 15 17 ]. Similar results were observed when LA-rich sources (sunflower and safflower) were included between 2% and 15% in the diet [ 18 20 ], but the dry matter intake (DMI) tended to reduce with 15% of safflower inclusion [ 20 ]. In that sense, Oliveira et al [ 21 ] observed that the inclusion of 30% of crushed sunflower caused a reduction of average daily gain (ADG) in heavy lambs, and worsen carcass characteristics.…”
Section: Unsaturated Fatty Acidssupporting
confidence: 53%
See 1 more Smart Citation
“…The inclusion of ALA-rich sources (linseed, chia seed and camelina oil) did not affect growth and carcass parameters, either in light [ 1 , 2 , 13 , 14 ] or heavy lambs [ 15 17 ]. Similar results were observed when LA-rich sources (sunflower and safflower) were included between 2% and 15% in the diet [ 18 20 ], but the dry matter intake (DMI) tended to reduce with 15% of safflower inclusion [ 20 ]. In that sense, Oliveira et al [ 21 ] observed that the inclusion of 30% of crushed sunflower caused a reduction of average daily gain (ADG) in heavy lambs, and worsen carcass characteristics.…”
Section: Unsaturated Fatty Acidssupporting
confidence: 53%
“…In contrast, linseed [ 2 , 14 , 27 ], canola oil [ 37 ], sunflower [ 21 , 38 ] and safflower oil [ 19 ] dietary supplementation did not affect meat color parameters. Moreover, it has been found that redness increased when 15% of safflower oil [ 20 ] or 150 mL/week canola oil [ 28 ] were supplemented, which can be related to the increased intake of α-tocopherol from safflower oil and of monounsaturated fatty acids (MUFA) from canola fed animals, acting as limiting factor for lipid oxidation of meat.…”
Section: Unsaturated Fatty Acidsmentioning
confidence: 99%
“…Incorporating vegetable oil into the diets of broiler chickens has been found to elevate the level of subcutaneous fat in these birds, as indicated by various studies. For instance, Wang et al ( 2017) conducted a study that revealed a significant increase in subcutaneous fat among broiler chickens fed a diet supplemented with vegetable oil in comparison to those fed a control diet (66). This rise in subcutaneous fat can have both advantageous and disadvantageous consequences for poultry producers.…”
Section: Discussionmentioning
confidence: 99%
“…Also Amer et al (15) reported that the safflower oil levels (0%, 1% and 5%) had no significant effect on the body weight gain, body weight, feed conversion ratio and feed intake of broiler chickens (P>0.05). Similarly Ferreira et al (20) investigated the intake, performance, carcass characteristics and meat quality of lambs fed finishing feeds containing 0%, 7.5% and 15% safflower seeds instead of corn and soybean meal.…”
Section: Discussionmentioning
confidence: 99%